Leukocytoclastic vasculitis presenting clinically as bullous pyoderma gangrenosum following leucovorin, fluorouracil and oxaliplatin chemotherapy: a rare case report and literature review. Issue 9 (9th August 2022) - Diab, Reem; Rakhshan, Azadeh; Kaddah, Ali; Abdollahimajd, Fahimeh; Mirzaei, Hamid Reza
Abstract : There are no published cases about bullous pyoderma gangrenosum induced by leucovorin, fluorouracil and oxaliplatin (FOLFOX) chemotherapy. With the increasing incidence of gastric and colorectal cancers and the increased usage of targeted therapies, some cutaneous adverse effects may become common. An 84-year-old male presented to our clinic with multiple ulcerative plaques covered with hemorrhagic crusts on both extremities after several FOLFOX chemotherapy sessions for gastric cancer and liver metastasis. Two weeks later, multiple bullae also appeared, especially on the acral areas. The histopathology examination was compatible with acute leukocytoclastic vasculitis. The FOLFOX chemotherapy regimen is increasingly administered considering the rising incidence of gastrointestinal cancers. Hence, our understanding of its possible side effects and complications must be heightened.